A REVIEW OF EFFICIENCY IMPROVEMENT OF HYDRO-TURBINE GENERATOR (Journal of Energy and Safety Technology (JEST), 2025)
Endowed with favorable topography and tremendous amount of rainfall annually, allowed Malaysia to boost its hydroelectric power plant with Bakun Hydroelectric Dam in Sarawak as the largest supplier of hydroelectric energy. Hydroelectric not only acts as flood mitigation but also an alternative of electricity that slowly replaces conventional electric sources like natural gases and coal. However, efficiency of hydro-turbine should be taken into consideration to minimize energy loss while simultaneously optimizing total output power.  The review also highlights major challenges, such as material limitations, infrastructure constraints, and the complexities of integrating artificial intelligence into control and optimization processes. Overall, the findings show that improving system efficiency requires simultaneous advancements in material selection, monitoring technologies, control strategies, and predictive tools to create more reliable and higher‑performing hydropower systems.
Keywords: hydroelectric power; hydro turbine efficiency; hydropower optimization; renewable energy